Total Joint Arthroplasty in Patients With Atrial Septal Defects: What Are the 90-Day Complications? - Jennifer Bido, MD, MPH; Simarjeet Puri, BS; Eduardo A. Salvati, MD; Michael B. Cross, MD; Alejandro Gonzalez Della Valle, MD; Elizabeth B. Gausden, MD, MPH (Arthroplasty Today, 2022)
Background: Congenital heart defects, such as atrial septal defects (ASDs) and patent foramen ovale (PFO), may increase the risk of embolic events in total hip or knee arthroplasty (THA/TKA). The objective of this study was to determine the 90-day incidence of intraoperative and postoperative embolic events and all other complications in patients with a known ASD/PFO who underwent primary hip and knee arthroplasty. Methods: This is a retrospective review of 160 patients with ASD/PFO undergoing 196 primary arthroplasties (94 THAs, 102 TKAs) at a single institution. The mean age was 64 years (standard deviation [SD] 11.1), 40.6% were male, and average body mass index was 31 kg/m2 (SD 7.2). The mean follow-up period was 19 months (SD 16). Forty-three percent of patients were on anticoagulation preoperatively. All patients received postoperative thromboprophylaxis (48% aspirin, 31% direct oral anticoagulants, 18% warfarin, 3% enoxaparin). Results: There were no embolic events identified. Fourteen patients (7%) developed complications within 90 days. Three had bleeding complications, and 8 had other nonoperative complications, which were all managed conservatively and had uneventful recoveries. Additionally, 3 patients had complications requiring reoperations: 2 for periprosthetic fractures (1 THA, 1 TKA) and 1 for a periprosthetic infection (TKA). Conclusions: In this cohort of patients with a known ASD/PFO undergoing THAs and TKAs, there were no cases of embolic events. However, it would be advisable to have a thorough cardiology evaluation to assess potential risks and benefits of defect repair prior to total joint arthroplasty and to reduce the risk of paradoxical embolic events and the necessity of potent anticoagulation. Level of evidence: Prognostic Level IV.